The Development of Independent Life Skills of the Children and Teenagers from Foster Home: Achievements, Challenges, Solutions - Samašonok, Kristina (Pedagogika, 2013)
Contemporary society is concerned about successful functioning of its members and their effective participation in social interrelations therefore the adaptation of children living in foster homes is perceived as a relevant social issue. In the context of developing democratic ideas increasing attention is being paid towards the problem of adaptive behavior and its development in children without parental care. It is influenced by important social, political, value and legal changes having occurred in the last several decades in Lithuania in a context of which the attitude towards children without parental care, their social status, foster care and development is also changing. While adopting more laws and resolutions on the issues of child’s foster care, development and healthcare there appear more possibilities to solve a lot of relevant questions in child foster care and training institutions. In the context of democracy increasing attention is paid towards social integration of children living in foster institutions, their involvement and participation into social life. The goals and objectives of Lithuanian educational system reflect the intention to prepare a person for life, who is able to analyze reality individually or with other people, also adequately deal with the problems, plan the future and successfully adapt to the constantly changing, dynamic society. These objectives allow to discover a variety of aspects of the organization of educational activities in foster homes. The problematic issue arises while preparing foster home pupils for independent living: Are the educational system and conditions at foster homes sufficient and adequate in process of preparation for independent life? The article actualizes the educational significance of preparing teenagers for independent life. Interviews with foster home staff evaluate the current situation of foster homes, disclose the education system, work achievements (strengths), discuss the developmental problems and identify deficiencies of preparation for independent living in foster homes. The aim – to assess the preparation of foster home pupils for independent living within the context of foster homes, revealing the positive and improvable aspects of the foster home educator’s point of view. Analyzing the features of foster home preparation for independent living in care institutions, the study involved 17 foster home staff, based on their opinion about their personal work experiences and points of view. In order to understand home educational activities, to review the pupils’ preparation for independent living opportunities, educational reality, to find out and identify problems, provide opportunities for improving the situation, the interview method was used. Instant analysis revealed that home care workers initiated a variety of activities: encourage children to solve problems, analyze situations and make decisions. It is also practiced by demonstration of adult example, analyzing the situation and promoting the search for solutions. Workshops are organized, situations and educational environment is created in which the pupils are encouraged to act independently, provide practical training skills that enable learners to try themselves in different activities (household work, cooking, etc.). However, according to the assessment of the current situation in foster homes, it is clear that there are not optimal functions performed by the formation of practical skills and preparing for independent living of children without parental care. Interviews revealed that foster homes lack „real practices“ when most children are able to buy food, count the money, pay for services, cook, and independence is developed mostly by the potential circumstances. Comments on the survey suggest that the lack of practical activities, funding and real-world examples in foster homes prevent realization of the set goals, implement ideas for youngsters to prepare for independent living, to acquire domestic skills and do not create conditions for independent personal development (learning). Discussing the opportunities for improvement of foster home preparation for independent living, almost unanimously expressed material financial base and the improvement of household demand. Foster home staff believes that the conditions under which pupils can cook themselves face with the real everyday life, keep their own budgets, learn, acquire new knowledge or skills may be one of the most successful assumptions for training (learning) to live independently when they came out foster homes.